Visual and ocular surface benefits of mini-scleral contact lenses in patients with chronic ocular graft-versus-host disease (GvHD) - Keye, Philip; Issleib, Susanne; Gier, Yvonne; Glegola, Mateusz; Maier, Philip; Böhringer, Daniel; Eberwein, Philipp; Reinhard, Thomas (Scientific reports, 2024)
Graft-versus-Host disease is a major complication of allogeneic stem cell transplantation. The eyes are a frequently affected organ with a severe dry eye disease being the hallmark manifestation. This retrospective study evaluates the effect of mini-scleral contact lenses on visual acuity, eye-related quality of life and the ocular surface. 62 eyes of 31 patients were included and visual acuity, ocular surface disease index (OSDI) questionnaire results and Oxford grades before and after mini-scleral lens fitting were compared. Median Snellen fraction with mini-scleral lenses was 20/25 (1st 20/30/3rd 20/20) compared to 20/40 median Snellen fraction with spectacles (1st 20/60/3rd 20/25). Median OSDI scores improved from 73 (1st 41.6/3rd 89) before fitting to 27 (1st 14.5/3rd 56) with mini-scleral lenses. Median Oxford grade decreased from 3 before mini-scleral lens fitting (1st 1/3rd 4.75) to 1 after mini-scleral lens fitting (1st 0/3rd 4). Median time of follow up was 717.5 days. Seven patients (22.6%) discontinued therapy with mini-scleral lenses. Mini-scleral lenses are beneficial for most patients with ocular GvHD as they improve visual acuity, eye-related quality of life and the integrity of the corneal epithelium.